Multidimensional Scaling Analysis Based on Factors Affecting Under-Five Malnutrition Cases in West Java - Rachman, Hallen Naafi Aliya; Putri, Nisa Akbarilah; Hendrawati, Triyani (STATMAT : JURNAL STATISTIKA DAN MATEMATIKA, 2025)
Malnutrition is a condition where the body's nutrition is below the average standard. Nutritional issues, particularly among toddlers, remain a serious problem in various provinces in Indonesia, including West Java. In 2022, 3.3% of toddlers in West Java experienced undernutrition, and 0.4% suffered from severe malnutrition. This study aimed to map 27 regencies/cities in West Java Province based on factors influencing toddler malnutrition in 2022, highlighting similarities among these areas. A statistical method, Multidimensional Scaling (MDS), was used to classify objects based on similar characteristics. This method illustrated the dispersion of observational units based on measured variables, creating a two-dimensional map. Nearby regencies/cities indicated similar malnutrition conditions among toddlers, suggesting that the same mitigation efforts could be applied in those areas. The analysis resulted in four quadrants. Red circles were used on the map to mark points that were very close. To test the validity, STRESS and R-Square values were calculated. The STRESS value of 0.012% indicates that the generated map is in the perfect category, demonstrating that this analysis has precise reliability and validity. The R-Square value of 99.76% shows that the variance of the data is well explained by the model. This indicates that the Multidimensional Scaling (MDS) model is acceptable for mapping purposes. The findings of this study serve as valuable information and a reference for the West Java provincial government to make more effective and targeted efforts in combating malnutrition.